The impact of exposure to the land of the Bible - Pienaar, D. N. (Old Testament essays, 1996)
In this article the attention is drawn to the impact of exposure to the land of the Bible as experienced mainly by the Israelites and the measures and systems they devised to survive in the arid parts of the country such as the Sinai and the Negev. Special attention is devoted to the run-off and diversion farming and chain of wells systems. As an afterthought it is suggested that it is necessary for a teacher/lecturer/professor to be exposed to these circumstances to be able to appreciate the accomplishments of the people of the Bible.